Pengembangan Produk Rotan Berbasis Nilai Tambah: Perspektif dan Kepuasan Konsumen di Rotan Rangga Kota Baru (Jurnal Multidisiplin West Science, 2025)
This research is motivated by the shift in market demand for rattan furniture, which not only needs to be functional but must also possess aesthetic and sustainability value. The objective is to analyze value-added product development strategies and the level of consumer satisfaction at Rotan Rangga Kota Baru. The study employs a qualitative approach (interviews and direct observation) for preliminary data and a descriptive quantitative approach using the Quality Function Deployment (QFD) and House of Quality (HoQ) methods for product planning. The results indicate that product development successfully enhances value-added through design innovation, quality materials, and production efficiency. The main factors influencing consumer satisfaction are quality, aesthetics, comfort, durability, and the aspect of environmental sustainability. Through HoQ analysis, the customer attribute with the highest importance is "Dilipat untuk lingkungan" (Foldable for the environment) (value 10), and the most influential technical factors are "Geometri Bentuk" (Shape Geometry) and "Sertifikat bahan baku" (Raw Material Certificate). Therefore, it is recommended that the development focus should be directed towards an ergonomic shape, high-quality material, and environmental sustainability orientation to optimally meet consumer expectations.
Keywords: Proses Produksi; Pengembangan Produk; Pemasaran dan Konsumen; House of Quality; Kota Baru